Strategi Reflektif Pendidikan Agama Kristen dalam Menanggulangi Krisis Identitas Generasi Z di Era Digital - Novida Dwici Yuanri Manik; Shalomita; Miranty Helena Adoe (JURNAL LUXNOS, 2026)
Identity crisis is a common problem among adolescents. In this case, Generation Z is in their teens and early adulthood. This problem arises from various factors, including rapid technological developments and a lack of self-understanding among adolescents. An identity crisis may initially have little impact on the adolescent or those around them, but if it persists, it can become a persistent problem that can have a significant impact on others, even the next generation. Therefore, education is expected to be a solution to this problem and phenomenon. Adolescents are taught to fully understand themselves in the eyes of God through the instilling of Christian values in Christian Religious Education subjects. This way, they understand their true identity and the purpose for which they were born into this world—of course, for a noble purpose. The method used in this study is descriptive analysis, which involves analyzing and describing it accurately. Christian Religious Education is one way to address the identity crisis that occurs among adolescents. The materials taught in Christian Religious Education serve as a means for adolescents to fully understand themselves before God.